IMPLEMENTASI MODEL SANTUN UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Rahmah Eka Putri; Yogi Prihandoko; Noorhapizah Noorhapizah; Darmiyati Darmiyati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the suboptimal critical thinking skills of grade VA students at SDN Kuin Selatan 1 due to the monotonous and minimally stimulating Pancasila Education learning process. The gap between the curriculum's demands for critical thinking and the reality of passive learning necessitates intervention. The focus of this research is to improve students' critical thinking skills on the topic